2007
DOI: 10.1016/j.jneuroim.2007.08.004
|View full text |Cite
|
Sign up to set email alerts
|

CSF proteomic fingerprints for HIV-associated cognitive impairment

Abstract: Cognitive impairment remains a major complication of advanced human immunodeficiency virus (HIV) infection despite the widespread use of anti-retroviral therapy. Diagnosis is made by exclusion making biomarkers of great potential use. Thus, we used an integrated proteomics platform to assess cerebrospinal fluid protein profiles from 50 HIV-1 seropositive Hispanic women. Nine of 38 proteins identified were unique in those patients with cognitive impairment (CI). These proteins were linked to cell signaling, str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
63
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 57 publications
(64 citation statements)
references
References 47 publications
1
63
0
Order By: Relevance
“…After SEC isolation, the (Lys) 6 -tagged rHbI was enzymatically digested with trypsin, and the generated peptides were identified by LC–MS/MS [37]. The analysis was performed in duplicate.…”
Section: Resultsmentioning
confidence: 99%
“…After SEC isolation, the (Lys) 6 -tagged rHbI was enzymatically digested with trypsin, and the generated peptides were identified by LC–MS/MS [37]. The analysis was performed in duplicate.…”
Section: Resultsmentioning
confidence: 99%
“…Similar results were obtained in the CSF of HAND patients and in HIV seropositive patients that are cocaine users where cathepsin B secretion and activity remained at the same levels between experimental and control groups. It has been established that HIV-1 transforms the monocyte plasma membrane proteome (Kadiu et al 2009) and proteomics analysis of CSF demonstrated that reduction of antioxidants enzymes such as Cu/Zn SOD and GPx, have been associated with disease severity (Laspiur et al 2007; Velazquez et al 2009; Angel et al 2012). It is quite possible that an antioxidant imbalance could promote secretion and neurotoxic activity of cathepsin B in the CNS.…”
Section: Discussionmentioning
confidence: 99%
“…In this context, it is of interest that recent proteomics studies have identified lysosomal enzymes (cathepsins) and related proteinases (cystatins) to be the ones most significantly altered in the CSF of cognitively impaired HIV ϩ individuals. 42 In vitro, HIV-infected mononuclear phagocytes display similar changes in cathepsins, cystatins, and other lysosomal enzymes, 43,44 suggesting that the altered metabolism of HIV-infected macrophages and microglia is central to the pathogenesis of HIV-associated neurocognitive disorder (HAND). Significant elevations of lysosomal hydrolases and cathepsins have been found in earlier tissue-based studies HIVE and SIV encephalitis.…”
Section: Discussionmentioning
confidence: 99%